A Clinical Study To Evaluate The Effect of Yashtavyah Niruha Vasti and Bodhi Vriksha Kashaya In The Management of Vatarakta w.s.r. To Gout. - Diksha; Bhardwaj, Anil; Singh, Pushpender (International Research Journal of Ayurveda & Yoga, 2021)
Introduction : Vatarakta is disease which is caused by vitiation of Vata and Rakta (blood). This disease usually caused by faulty life style1. It can be compared with Gouty arthritis due to maximum resembles in the sign and symptoms. In this era Vatarakta (Gout) is very eminent disease with lesser effective treatment. Along with life style modifications effective therapy is the need of the day. Present research work was humble attempt to see the effect of Panchkarma and Shaman aushadh (Pacification therapy) in this disease. Methods : In this study 10 patients of Vatarakta (Gout) were selected from OPD of Panchkarma department, RGGPG Ayurvedic college and Hospital Paprola. All patients were treated with Yashtavyah Niruha Vasti along with Bodhi vriksha kashaya panam. Result: The Vasti and Bodhi Vriksha Kashaya were significantly effective in all the symptoms of Vatarkta. Discussion: Vata and Rakta are the main Dosha and Dushya in disease. Vasti (enema) being most effective in Vata Dosha and Yahtvyah which is main content of Vasti causes Rakta Shaman. Boshivriksha Kashya is effective in Tridosha Prakopa. Thus, this protocol was found significantly effective.